Attitudes toward suicide: A comparison between urban and rural dwellers in Ghana - Emma Sethina Adjaottor; Daniel Kwasi Ahorsu (Wolters Kluwer Medknow Publications, 2020)
Introduction: Appropriate attitudes toward suicide (ATTS) is key to preventing suicide, a major mental health challenge worldwide. Hence, this study examined the differences between urban and rural dwellers on ATTS (in total and across the subscales - principal attitude (suicide as a right), representations of intentionality, tabooing, preventability of suicide, and knowledge (myths about suicide). Methods: A cross-sectional survey design was used in this study. A convenient sampling technique was used to select 400 respondents from urban (n = 200) and rural (n = 200) areas. A questionnaire packet comprising a self-designed demographic section and valid ATTS scale was used for the data collection from respondents (urban and rural dwellers). Descriptive (frequency and percentages) and inferential (independent t-test) statistics were used to analyze the data using SPSS software. P < 0.05 was considered statistically significant. Results: Both urban and rural dwellers were found to have negative ATTS with urban dwellers (131.40 ± 10.75) having significantly more negative ATTS (P = 0.000) than rural dwellers (118.59 ± 13.62). Furthermore, urban dwellers were found to have significantly more negative attitudes toward principal attitude (suicide as a right), representations of intentionality, tabooing, preventability of suicide, and knowledge (myths about suicide) than rural dwellers (P = 0.000). Conclusion: Settings influence ATTS such that urban dwellers have become more informed and more prepared to help prevent suicide compared with their rural counterparts.